Serum Tumor Necrosis Factor Alpha and Gene Polymorphisms in Rheumatoid Arthritis Patients in Babylon Province, Iraq - Abdulsamie H. Alta'ee (Journal of Global Pharma Technology, 2018)
Background: Rheumatoid arthritis (RA) is a systemic autoimmune disease affects 0.5-1% of the worldwide population, of unknown etiology, characterized by chronic inflammation of the synovial joints, hyperplasia, and overgrowth of synoviocytes, with the destruction of articular cartilage that can cause serious weakness and inability to work. Objective: The present study aims to investigate the possible association between tumor necrosis factor alpha (TNF-α) levels and (-308 G/A) TNF-α promoter polymorphism in patients with RA in Babylon Province. Patients and Methods: This study was designed as a case control. Forty-five (10 males, 35 females) patients with RA and forty-five (9 males, 36 females) apparently healthy persons as control with the compatible age and sex were enrolled in this study. Serum level of TNF-α and anti-cyclic citrullinated peptide antibodies (ACCPA) were measured using enzyme-linked immunosorbent assay (ELISA) method. Disease activity of RA patients was assessed using the Disease Activity Score-28 (DAS28). The frequency of TNF-α -308 G/A gene polymorphism was determined using polymerase chain reaction, restriction fragment length polymorphism (PCR-RFLP) technique. Results: Present study finds significant high levels of serum TNF-α and ACCPA in patients with RA in comparison with healthy controls. The genotype of (-308 G/A) TNF-α gene promoter polymorphisms the GG genotype was 60% in RA patients and 42.2% in control group, while the GA genotype was 40% in RA patients and 53.3% in control group, whereas, the AA genotype was 0% in RA patients and 4.4% in control group. Correlation between TNF-α levels with both of DAS-28 and ACCPA in RA patients found to be a significant positive correlation proposes a probable role of TNF-α in RA pathogenesis. Statistical analysis showed no significant difference in the genotype frequency of the TNF-α (-308 G/A) gene promoter polymorphisms between two groups. Conclusions: The results of the present study were shown that TNF-α (-308G/A) gene polymorphism had not associated with a risk factor of RA in Babylon patients and this SNP do not affect the serum level of TNF-α in RA patients.Keywords: Rheumatoid arthritis, TNF-α, -308 G/A gene polymorphism, ACCP Antibody, PCR-RFLP , Iraq.